Las limitaciones de la tipificación de infracciones en materia de fauna silvestre, a propósito del procedimiento administrativo sancionador iniciado contra la refinería La Pampilla - García Cerrón, Erick Leddy (2022)
The oil spill in the Ventanilla sea has posed a great challenge for the public entities responsible for managing this environmental disaster. In addition, different voices of public opinion are demanding that La Pampilla Refinery, owned by Repsol, assume its responsibility, among other aspects, for the serious damage caused to wildlife. In this context, the National Forestry and Wildlife Service, through the Technical Forestry and Wildlife Administration of Lima, initiated an administrative sanctioning procedure against the company, accusing them of acting cruelly and causing the death of marine wildlife specimens. However, this action, which could be considered as an indispensable measure to achieve justice in the face of the serious damage caused to our natural resources, could end up becoming a serious setback in the State's search for environmental justice. From the analysis of the principle of typicity for the exercise of the administrative sanctioning power and the legislation on wildlife, it is evident that it would not have adequately regulated events such as those triggered because of the oil spill. These inconsistencies are evidenced in the process for the precise delimitation of the infringing conduct, which, by presenting gaps at the level of the substantive norm, ends up limiting and projecting a scenario regarding the possibility of declaring administrative responsibility and imposing the corresponding sanction for harming our wildlife.